Numerical Prediction of Welding Distortion Considering Gravity Force on General Ship Grillage Structure by Elastic Finite Element Method Using Inherent Strain - Donghan Woo; Mitsuru Kitamura (Journal of Marine Science and Engineering, 2020)
The accurate numerical prediction of welding deformation is important to improve the structural safety of ships and offshore structures in heavy industries. The precise reflection of the real working condition in the numerical prediction is an essential factor to improve its result. In the present study, the effect of the gravity force on numerical prediction of the optimal welding sequence of a general ship grillage structure was validated with the introduction of a new boundary condition in which the structure is placed over rails. Additionally, the direction of the gravity force of welded structures could be changed at the final assembly process according to the production plan. The effect of the gravitational orientation on the final welding displacements was also investigated herein. The elastic finite element method using the inherent strain, interface element, and multipoint constraint function was introduced to analyze the welding deformation. This study validated the influence of the gravity force on the numerical prediction of welding displacements in a general ship grillage structure.